2016
DOI: 10.14238/sp15.3.2013.167-73
|View full text |Cite
|
Sign up to set email alerts
|

Peran Eritromisin terhadap Toleransi Minum Bayi Prematur

Abstract: Latar belakang. Eritromisin merupakan salah satu obat prokinetik untuk mengatasi intoleransi minum pada bayi prematur karena imaturitas sistem pencernaan. Beberapa penelitian mengenai efektifitas eritromisin dalam mengatasi intoleransi minum akibat imaturitas saluran cerna masih merupakan kontroversi.Tujuan. Mengetahui peran eritromisin dalam meningkatkan toleransi minum bayi prematur.Metode. Penelitian uji kinis prospektif acak terkontrol tersamar ganda pada bulan September 2011-Februari 2012 dengan subyek ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…in preterm infants compared to placebo. 4 In this study, we found no significant difference in the use of high-dose erythromycin as prophylaxis for feeding intolerance in preterm infants <37 weeks, compared to placebo. Two types of motilin receptors (neural and smooth muscle) have been found and the efficacy of erythromycin depends on the dose and gestational age.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations
“…in preterm infants compared to placebo. 4 In this study, we found no significant difference in the use of high-dose erythromycin as prophylaxis for feeding intolerance in preterm infants <37 weeks, compared to placebo. Two types of motilin receptors (neural and smooth muscle) have been found and the efficacy of erythromycin depends on the dose and gestational age.…”
Section: Discussioncontrasting
confidence: 48%
“…In addition, the use of domperidone in preterm infants remains controversial. 3,4 Erythromycin is an antibiotic also commonly used to treat feeding intolerance in preterm infants. This macrolide has a motilin-like effect and stimulates peristalsis.…”
mentioning
confidence: 99%
See 1 more Smart Citation